Minat Baca Siswa Sekolah Dasar di Depok: Studi Kasus di SDN Anyelir 1 Depok Jaya - Rachman, Margareta Aulia; Rachman, Yeni Budi; Rachmawati, Yuliana Mukti (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2017)
This study aims to describe reading habits of elementary school student at Sekolah Dasar Negeri Anyelir 1 Depok Baru, Jawa Barat. This is a quantitative research with case study method. The data collected by distributing questionnaire towards 8 years old of 152 students at the particular school (total sampling population). The result shows that reading habit level of participants are categorized low. Less than 55% participants claimed they spent their leisure time for reading. This research suggest that parents and school teacher need to cultivate reading habit of the kids. Book habits among children also needs to be preserved as well as providing good children books.